Perancangan Antarmuka Pengguna Sistem Informasi Penilaian Siswa Menggunakan Human Centered Design (HCD) (Studi Kasus: SMP Islam Sabilurrosyad Malang) - Sania Nur Agustina; Ismiarta Aknuranda; Alfi Nur Rusydi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Sabilurrosyad Islamic Junior High School has implemented a 2013 curriculum system in teaching learning activities. Likewise with the student assessment process. Sabilurrosyad Islamic Junior High School students get a report on the results of learning at the end of each month and end of the semester. Therefore, the school cannot use the report system provided by the government because it uses the Microsoft Excel application. The collection of grades given by teacher educators to the class teacher is often delayed and here the class teacher must copy the grades ​​before printed in the form of report. It results the inefficiently of time. Based on these problems, the researchers designed an information system user interface to help the student assessment process be easier and more efficient. The design of the user interface is done by using the Human Centered Design (HCD) approach to produce designs that suit the needs and requirements of users so as to achieve user satisfaction. The results of this research are two high fidelity prototype designs that were evaluated by 3 people of prospective users. Testing is done by using usability testing and Single Ease Question (SEQ) assessments. This questionnaire assessment measures the level of user convenience in doing a task. The results of the SEQ questionnaire assessment indicate that design one and design two are easy to use and accepted by prospective users.